Antimicrobial Effects of Egyptian Local Chicory, Cichorium endivia subsp. pumilum - Ahmed M. Amer (International Journal of Microbiology)
The discovery of novel and more efficient antimicrobial agents from natural sources like plants is one of the most important ways through which the growing threat of antibiotic-resistant pathogens can be overcome. Herein, we report the potential antimicrobial activity of Cichorium endivia L. subsp. pumilum. Different concentrations of various solvent extracts prepared from several parts of chicory were tested for their antimicrobial effect against a panel of microorganisms. The antimicrobial activity was analyzed using the well diffusion method, where zones of inhibition were used as indicators of antimicrobial activity. The results indicated the superiority of seed extracts over both leaf and root extracts. Methanol extracts showed higher activity compared with chloroform and water extracts. Increased solvent extract concentration was accompanied by a parallel increase in the diameter of the inhibition zone. Gram-positive bacteria were found to be more sensitive than Gram-negative bacteria and fungi. On a whole, the highest observed inhibition zones (21.3 ± 0.6 and 20.1 ± 0.4 mm) were recorded with the methanolic extract of chicory seeds against S. aureus and B. cereus, respectively. These results offer insights into the antimicrobial potency of this Egyptian local plant and provide a basis for further phytochemical and pharmacological research.